PENGARUH BOKASHI KOTORAN SAPI PADA BERBAGAI BIOAKTIVATOR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium. ascalonicum L.) - Brigita Kourow; Lani Pelia; Hertasning Yatim; Nurmasyitah Mambuhu (Fakultas Pertanian Universitas Tompotika Luwuk, 2022)
Bokashi cow dung is a fertilizer derived from fermented cow dung with various bioactivators that can improve soil physical and structural properties, increase water holding capacity, soil chemistry and soil biology. The aim of the study was to identify and study cow dung bokashi on various bioactivators on the growth and yield of shallots. This research will be carried out from September to November 2021 on the farmers' land in Nulion Village, South Totikum District, Banggai Islands Regency. This study used a randomized block design (RBD) consisting of 4 treatment levels, namely B0: Control (no treatment); B1: Bokashi cow manure + Trichoderma sp bioactivator; B2: Bokashi cow dung + EM4 Bioactivator; B3: Bokashi cow dung + ABG Degra Bioactivator. Each treatment was repeated 5 times so that there were 20 experimental units. The results showed that the treatment of giving cow dung bokashi to various bioactivators had a very significant effect on plant height, number of leaves, number of tillers, fresh weight per sample, fresh weight per plot, dry weight per sample, there was one bioactivator which had a very significant effect and had the highest average value on shallot growth and yield was Trichoderma sp.